Implementasi Prinsip Check and Balances di Indonesia - Husni Thamrin; Maria Ana Liwa; Eka Ariska Ady S; Doni Fitra (Collegium Studiosum Journal, 2020)
This study aims to analyze the separation of powers in the Indonesian constitutional system, as well as to analyze the principles of checks and balances in the Indonesian constitutional system. This research is a normative study, using a statutory approach, a conceptual approach, and a historical approach, the data used are primary and secondary legal materials, all data collected were analyzed qualitatively. The results show that the authority given to the Public Prosecutor is an authority in the form of a mandate, considering that this authority is the delegation of authority between superiors and subordinates at a hierarchical level, the development of that authority is seen from its purpose and designation in accordance with the contents of the mandate transfer. given by the Attorney General to his subordinates and usually has a special formal nature, one of which is the special mandate given by the Attorney General to his subordinates (the General Prosecutor) in the case of delegation of authority in the form of extraordinary legal remedies or reconsideration in criminal cases.